Hall Current Effect in MHD Oscillatory Couple Stress Dusty Fluid through an Inclined Saturated Permeable Channel - Govindarajan, A.; Vijayalakshmi, R. (International Journal of Engineering and Technology, 2018)
This paper aims to study the Hall current effect in MHD (Magneto Hydro Dynamics) oscillatory couple stress dusty fluid (blood) flowing through an inclined permeable medium channel. A mathematical model for both the fluid and particle phases are framed based on the conservation laws. The exact form of solutions for velocity, energy, species concentration profiles are got by solving the corresponding partial differential equations. To have a better knowledge about the problem, quantitative estimates are presented pictorially and discussed to know the main features of different measurable factors like radiation, Hall current, Schmidt number, Nusselt number etc.Â Â